2021
DOI: 10.1016/j.gastre.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of SARS-CoV-2 infection in patients scheduled for digestive endoscopy after the peak of the first wave of the pandemic

Abstract: Healthcare professionals in endoscopy units have a possible risk of SARS-CoV-2 infection by different routes: inhalation of airborne droplets, aerosols, conjunctival contact and faecal-oral transmission. Objective To describe the detection of SARS-CoV-2 in a series of patients scheduled for digestive endoscopy at the Hospital Santa Caterina, Salt, (Girona). Methods Descriptive study of a series of cases of patients scheduled for endoscopy during the month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
“…Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164]. The types of included studies changed across the five versions of the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a patient has a positive or inconclusive RT-PCR test, the procedure should be considered high risk and should only be conducted if the clinical situation demands ( 27 ). Furthermore, if a patient has current symptoms or is otherwise at high risk for current infection ( Table 1 ), but has such an urgent indication for endoscopy that there is inadequate time to have a nasopharyngeal swab, then their procedure should also be considered high risk ( 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…While some early reports suggested that there was a low risk of COVID-19 transmission consequent to GI endoscopy ( 5 ), other reports indicated a high prevalence of SARS-CoV-2 infection in patients scheduled for digestive endoscopy ( 6 ). These contradictory reports resulted in confusion and uncertainty in decision making.…”
Section: Introductionmentioning
confidence: 99%